Pengembangan Media Pembelajaran Interaktif Berbantuan Adobe Flash Cs6 Pada Mata Pelajaran Teknologi Perkantoran di Kelas X OTKP SMK Negeri 1 Lamongan - Luluk Indah Wati; Jaka Nugraha (Universitas Negeri Surabaya, 2020)
Learning media can be used as a support for teaching and learning activities in class. The study was conducted to find out media development, analyze the feasibility of the media, and students' responses to the learning media developed, learning media was developed in office technology subjects in class X OTKP SMKN1 Lamongan. This type of research is R&D in order to create a product. This study adapted the 4-D model by Thiagaran, there are 4 stages, namely the first stage define, the second stage of design, the third stage of develop, the fourth stage of desseminate. Researchers conducted the research until the develop stage because the desseminate was carried out on a broader scale. Data collection instruments in this study consisted of a material & media expert validation questionnaire, and an online student response questionnaire. The validation of the material by the lecturer of the Study Program Office Administration Education Unesa, while the validation of media experts by the multimedia teacher of SMKN 1 Lamongan. The subjects of this interactive learning media were students X OTKP industry and X regular OTKP of SMKN 1 Lamongan, tested on 20 students chosen by random sampling. The results of evaluating the material validator got a percentage of 92% with the category